Information technology and its impact over sales function: a case study - Martinez, Marcelo Ferreira; Mattar, Fauze Najib (Revista da FAE, 2016)
Information Technology (IT) has become a crucial factor in the successful administration of the data flow by offering competitive advantages in the identification and cut of activities with no added value, in the integration of suppliers and partners and in the interaction and communication with customers. Thus this study – which focused on the customer – aims at analyzing the contribution of IT to the sales function, by means of a qualitative survey made with the direct customers of a paper industry with an important share in the Brazilian market. The survey indicates that, despite the good impression the customer had of the company’s services and products, its IT was underused, especially the remote access facility, although the customer wanted to use it to establish regular contact with the company. People and processes are a hindrance to the use of IT, which means that the company must not only invest in the syst